Geothermometry and Compositional Variation of Fluid Inclusions from the Tennant Creek Gold-Copper Deposits, Northern Territory, Implications for Exploration of Auriferous Ironstones - Huston D. L; Large R. R; Mernagh T; Ryan C. G (The Australasian Institute of Mining and Metallurgy, 1994)
The Tennant Creek goldfield is one of the largest gold producing districts in Australia, and major deposits, including Gecko, Juno, Orlando, Peko, Warrego, Nobles Nob, Golden Forty, Argo, TC 8 and White Devil have produced more than four million ounces of gold over the past two decades. Gold-copper-bismuth mineralisation at Tennant Creek occurs in lenticular, ellipsoidal or pipe-like bodies of magnetite-hematite ironstones which are hosted in turbiditic sedimentary rocks of Proterozoic age (Large, 1975; Wedekind, Large and Williams, 1989; Le Messurier, Williams and Blake, 1990; Morrison, Donnellan and Hussey, 1992).